Affiliate Activities on the Tiktok Shop Platform in Consumer Protection Law and Sharia Economic Perspective - Nugraha, Tisna; Adawiyah, Endah Robiatul (Strata Social and Humanities Studies, 2025)
This study seeks to analyze the conformity of business practices on TikTok Shop with Law Number 8 of 1999 concerning Consumer Protection and the principles of Islamic economics. The research adopts a qualitative approach with a normative juridical method, focusing on a literature review of Islamic economic law, consumer protection regulations, and relevant studies on electronic transactions. Data analysis was conducted thematically using the Miles and Huberman interactive model to capture recurring patterns and core issues. The findings demonstrate several weaknesses in current practices, including inadequate product information disclosure, limited transparency of additional costs, and underdeveloped consumer complaint mechanisms. From the perspective of Islamic economics, the study also identifies the presence of gharar (uncertainty), riba (usury), and exploitation, which contradict the values of justice, transparency, and accountability. This research contributes to the broader discourse on digital consumer protection by integrating legal and sharia perspectives. It provides both theoretical insight and practical recommendations for strengthening regulation, enhancing consumer awareness, and building a fairer and more ethical e-commerce ecosystem aligned with Islamic principles.